1992
DOI: 10.1055/s-2008-1071319
|View full text |Cite
|
Sign up to set email alerts
|

Two Brothers with a Variant of Hereditary Sensory Neuropathy

Abstract: We report two brothers with the clinical symptoms and neuropathological findings of hereditary sensory and autonomic neuropathy (HSAN) type IV but with normal sweating function and absence of recurrent fever. We propose that our patients may have a lower degree of expression of the genetic defect underlying HSAN type IV or that they represent a separate genetic entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1992
1992
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The diagnosis is generally established during early childhood when the family refers to a physican with such symptoms as loss of pain reception and trauma. The disease has no specific treatment, nor is its prognosis good ( Amir et al ., 1985 ; Bye et al ., 1990 ; Pavone et al ., 1992 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis is generally established during early childhood when the family refers to a physican with such symptoms as loss of pain reception and trauma. The disease has no specific treatment, nor is its prognosis good ( Amir et al ., 1985 ; Bye et al ., 1990 ; Pavone et al ., 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pavone et al (1992) reported cases in which sweating functions were normal but which were described as type 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we report the clinical course of three sibs with CIPA with one case being followed up over 25 years. In two patients, symptoms at diagnosis were first described in 1992 [10]. They showed the pertinent clinical findings of CIPA ( Table 1); during the follow-up there were no signs of increasing neurological morbidity and the acquired abilities were stable while self-help abilities had been improving.…”
Section: Discussionmentioning
confidence: 88%
“…The patient was a 22-year-old man, the first child of healthy consanguineous parents (first cousins), who was previously reported as two brothers with a variant of hereditary sensory neuropathy [Pavone et al, 1992]. His clinical phenotype was described as a variant form of CIPA because a sural nerve biopsy showed neuropathological findings consistent with this disorder but with normal sweating function and absence of recurrent fever.…”
Section: Introductionmentioning
confidence: 97%